2002
DOI: 10.1207/s15374424jccp3103_04
|View full text |Cite
|
Sign up to set email alerts
|

Response Styles Theory: Downward Extension to Children

Abstract: Describes partial support found for the downward extension of Nolen-Hoeksema's response styles theory of depression to preadolescents (N = 201). A self-report measure of response styles was developed. Evidence for the multidimensionality and independence of rumination and distraction is provided, as well as support for the reliability and validity of the new measure. Results supported 2 primary tenets of the theory: sex differences in ruminatory tendencies and associations between response styles and self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(71 citation statements)
references
References 30 publications
4
66
1
Order By: Relevance
“…This finding is in line with previous research on adolescents, demonstrating that girls are more likely than boys to engage in ruminative responses style (Bastin et al, 2014;Burwell & Shirk, 2007;Lopez et al, 2009;Mezulis et al, 2011;Muris et al, 2004;Rood et al, 2009;Verstraeten et al, 2010;Ziegert & Kistner, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in line with previous research on adolescents, demonstrating that girls are more likely than boys to engage in ruminative responses style (Bastin et al, 2014;Burwell & Shirk, 2007;Lopez et al, 2009;Mezulis et al, 2011;Muris et al, 2004;Rood et al, 2009;Verstraeten et al, 2010;Ziegert & Kistner, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, the relation between sadness rumination and depression has not been found to differ significantly for women and men. The strong association between sadness rumination and depression found in adults has also been found in adolescents (Park, Goodyer, & Teasdale, 2004;Silk, Steinberg, & Morris, 2003) and preadolescents (Ziegert & Kistner, 2002). Further, adolescent girls (Broderick & Korteland, 2002;Schwartz & Koenig, 1996) and preadolescent girls (Broderick, 1998;Ziegert & Kistner, 2002) report more sadness rumination than boys even when controlling for depressive symptoms.…”
mentioning
confidence: 77%
“…Among children and adolescents there is equivocal evidence for the gender difference in rumination. A number of studies have found that girls ruminate more than do boys (Broderick, 1998;Grant & Compas, 1995;Hart & Thompson, 1996;Schwartz & Koenig, 1996;Ziegert & Kistner, 2002), but a subset of those studies failed to support the hypothesis that such differences would account for gender differences in depressive symptoms (e.g., Grant & Compas, 1995;Schwartz & Koenig, 1996). In addition, several studies have not found gender differences in rumination among children and adolescents (Abela et al, 2004;Broderick & Korteland, 2004).…”
Section: Subtypes Of Rumination Inmentioning
confidence: 99%